Comparison of natural coarse aggregate and recycled coarse aggregate in concrete - Khairul Muzzamil Azmi (School of Environmental Engineering, University Malaysia Perlis, 2013)
This research to identify and compared the properties of natural coarse aggregate (NCA) and recycled coarse aggregate (RCA).